Mathematical question retrieval for web-based question-answering - Gayathri Gopalakrishnan (2014)
Mathematics is an essential subject, which can be applied in various areas of expertise. Thus, excelling in this core subject would help Secondary School students to adapt themselves better to the mathematical skills required for further education as well as for employment. Traditionally, books serve as the main source of information and practice exercises as students prepare for the ‘A’ - level and ‘O’ – level examinations. However, with the recent rapid expansion in the applications of the Internet and mobile devices, students and educators are looking to online resources to guide them in their preparation for examinations. Thus, the main aim of this project is to develop a web – based mathematical question retrieval system for question – answering specifically for educational purposes.